Malnutrition in developing countries: nutrition disorders, a leading cause of ill health in the world today. Issue 9 (September 2019) - Adepoju, Akinlolu A.; Allen, Stephen
Abstract: Shockingly, malnutrition remains a dominant cause of mortality, morbidity and lost potential in today's children. In 2017, more than 1 in 5 children did not achieve their growth potential and were at risk of the associated long-term deficits in cognitive development. Stunting affects almost 40% of children in South Asia and the number of stunted children in Africa is rising. More than 1 in 14 of the world's children are wasted. Forty-five percent of all deaths in under-fives are attributable to undernutrition. Meanwhile, overweight affects 1 in 20 of the world's children. One in four overweight children live in Asia and numbers are expected to increase. Management of severe acute malnutrition (SAM) is a huge challenge in low resource healthcare settings and mortality rates remain high. Current interventions to prevent malnutrition have limited impact. More effective prevention and treatment of malnutrition is needed urgently.